Predictors of Weight Loss in early treated Parkinson’s Disease from the NET-PD LS-1 cohort - Wills, Anne-Marie (J Neurol, 2017)
IMPORTANCE: Weight loss is a common symptom of Parkinson’s disease and is associated with impaired quality of life. Predictors of weight loss have not been studied in large clinical cohorts. We previously observed an association between change in body mass index and change in Unified Parkinson’s Disease Rating Scale (UPDRS) motor and total scores. OBJECTIVE: To explore predictors of weight loss in a large prospective clinical trial cohort of early treated Parkinson’s disease. METHODS: Secondary analysis of longitudinal data (1–6 years) from 1619 participants in the NINDS Exploratory Trials in PD Long-term Study-1 (NET-PD LS1). This was a double-blind randomized placebo controlled clinical trial of creatine monohydrate 10 gm/day in early treated PD (within 5 years of diagnosis and within 2 years of starting dopaminergic medications). Linear mixed models were used to estimate the effect of baseline clinical covariates on weight change over time. RESULTS: On average, participants lost only 0.6 kg per year. Higher age, baseline weight, female gender, higher baseline UPDRS scores, greater postural instability, difficulty eating and drinking, lower cognitive scores and baseline levodopa use (compared to dopamine agonists) were all associated with weight loss. Surprisingly baseline difficulty swallowing, dyskinesia, depression, intestinal hypomotility (constipation) and self-reported nausea/vomiting/anorexia were not significantly associated with weight loss in this cohort of early treated Parkinson’s disease patients. CONCLUSIONS: On average, participants with Parkinson’s disease experience little weight loss during the first 1–6 years after starting dopaminergic replacement therapy, however levodopa use and postural instability were both predictors of early weight loss.